Naturalistic acquisition in an early language classroom - Dahl, Anne; Vulchanova, Mila D. (Frontiers in Psychology, 2014)
This study investigated whether it is possible to provide naturalistic second language acquisition (SLA) of vocabulary for young learners in a classroom situation without resorting to a classical immersion approach. Participants were 60 first-grade pupils in two Norwegian elementary schools in their first year. The control group followed regular instruction as prescribed by the school curriculum, while the experimental group received increased naturalistic target language input. This entailed extensive use of English by the teacher during English classes, and also during morning meetings and for simple instructions and classroom management throughout the day. Our hypothesis was that it is possible to facilitate naturalistic acquisition through better quality target language exposure within a normal curriculum. The students' English vocabulary knowledge was measured using the Peabody Picture Vocabulary Test, version 4 (PPVT-IV, Dunn and Dunn, 2007a), at the beginning and the end of the first year of school. Findings are that (1) early-start second-language (L2) programs in school do not in themselves guarantee vocabulary development in the first year, (2) a focus on increased exposure to the L2 can lead to a significant increase in receptive vocabulary comprehension in the course of only 8 months, and (3) even with relatively modest input, learners in such an early-start L2 program can display vocabulary acquisition comparable in some respects to that of younger native children matched on vocabulary size. The overall conclusion is that naturalistic vocabulary acquisition is in fact possible in a classroom setting.